Influencia De La Educacion Inclusiva En El Aprendizaje De Los Niños Con Necesidades Especiales En El Sub Nivel 2 De La Unidad Educativa Francisco Huerta Rendón - Zuñiga Izquierdo, Barbara Yomara (2021)
Inclusive education isanissue around the world that, withthepassage of time, has beenupdated, sinceitisanissuethatisexperienceddaily in differentpoints, situations, and places, thishelps to deploywaysfor personal development, social, cultural and educational of the, in additionthatitistrying to developways to raiseawareness. Teachersfacedailychallenges to providequalityteaching, especiallyifitis inclusive teaching, sincetheintegration of childrenwithspecialneeds in institutionsis a rightforthem and anobligationfortheorganization. Sincechildrenwithspecialeducationalneeds are difficult to be understood, identified and treated in Ecuador. Thestudent, whopresentsSpecialEducationalNeeds, requiresthat curricular adaptations be madebasedontheirneeds, withtherespectiveparticipation of experts, so thatthesemodifications can developthevariouscapacities and skills of thestudent, allowingtheteacher to fulfilltheirobjective of education and learning. Thatiswhythisresearchprojectaims to supportchildrenwithSpecialEducationalNeeds, makingknowntheinfluence of inclusive education in thelearning of childrenwithspecialneeds at sub-level 2, so thatthey are allowed to be in aneducationalenvironment, managing to improvetheirquality of life and that of theirfamily.